PERANCANGAN KEDAI KOPI LUWAK TEMPO DULU DI TEGALALANG (Jurnal iSpectrum, 2023)
Luwak coffee is an Arabica type of coffee that uses coffee beans taken from the digestion of civets/coconut civets. These coffee beans are believed to have a different taste after going through fermentation in the civet's digestive tract. The uniqueness of Luwak coffee which has become world famous is important to preserve. It is hoped that the design of the Luwak coffee shop in an old style can be an alternative amidst the rise of modern style coffee shops, both in terms of packaging, presentation and interior design. This is also to introduce the public to Kopi Luwak itself as a treasure of Indonesian culinary culture. The design of this Luwak coffee shop will feature a rustic theme which will be combined with the Old Balinese concept. The choice of this concept theme aims to create a natural luwak coffee shop atmosphere, which can be seen from the use of dominant materials using wood, bamboo and other natural materials, which will create a design with an old school atmosphere in Bali that is still traditional.